Limites politiques et barrières sociales dans le monde maya classique - Dominique Michelet (Ateliers d'Anthropologie)
The archaeology of the Maya Lowlands of the classical era is rich in data that are likely to have something to teach us about several types of sociopolitical “boundary”. Although research since the 1970s has consciously aimed to address the question of the territorial limits of classical-world political entities, many other elements of sociopolitical partitioning exist, but they have tended not to receive the attention they deserve. The examination of a few pieces of information, borrowed from the results of recent collective research projects, indicates that more-or-less thin formal demarcations must have been rare, that there would even have been few explicit boundary markings, and that the thresholds were endowed with a certain thickness, their crossing obeying precise codes and/or involving ritualised behaviours.